Numerical analysis on the effects of manifold design on flow uniformity in a large proton exchange membrane fuel cell stack. (15th February 2023) - Xia, Yuzhen; Hu, Yiwei; Hu, Guilin; Lei, Hangwei; Lu, Jiazhou; Wang, Zichen; Wang, Qianpu
Abstract: The size and configuration of manifold can affect the flow characteristics and uniformity in proton exchange membrane fuel cell (PEMFC) stack; then its efficiency and service life. Based on the simulation results of a single fuel cell considering electrochemical reaction, a stack model with 300 porous media is established to numerically investigate the performances of a large commercial PEMFC stack. The effects of manifold width and configuration type on the pressure drop and species concentration are studied by computational fluid dynamics (CFD). The results show that the uniformity for most cases of U-type configuration is better than those of Z-type configuration. For U-type configuration, a very good uniformity can be obtained by selecting anode inlet manifold width of 20 mm and anode outlet manifold in range from 25 to 30 mm; the uniformity is bad for all cathode inlet manifold width, relatively better uniformity can be achieved by adjusting cathode outlet manifold width. For Z-type configuration, bad uniformity is found for cathode inlet and outlet manifold with all width; a relatively good uniformity can be obtained with suitable anode manifold width of 35 mm. The research can provide some references to improve gas distribution uniformity in large PEMFC stacks. Highlights: A simplified stack model composed of 300 porous media stack is developed. The effects of manifold size and manifold configuration are investigated. The uniformity for most cases of U-type configuration is better than Z-type. The optimum inlet and outlet manifold widths for anode and cathode are obtained.